Dual-use open cycle ocean thermal energy conversion (OC-OTEC) using multiple condensers for adjustable power generation and seawater desalination. (January 2016) - Kim, Albert S.; Kim, Hyeon-Ju; Lee, Ho-Saeng; Cha, Sangwon
Abstract: Multiple condensers are used for dual-use open cycle ocean thermal energy conversion to generate both electric power and desalinated water with preset ratios. Fundamentals of heat and mass transfer phenomena are scrutinized to identify optimal operational conditions of various OC-OTEC plant scales. Important control parameters include warm water temperature and its intake rate, vacuum pressure in the evaporator, and cold water temperature. Intake rate of the cold deep seawater is estimated based on the operational mode and conditions. Performances of the multiple condenser OC-OTEC system, power generation and seawater desalination capacities are analytically evaluated in terms of steam flow fractions, temperature of intake seawater, and vacuum pressure. This research provides unprecedented levels of theoretical depth, mathematical details, and design criteria for highly optimized dual-use OC-OTEC operations. Future research directions for OC-OTEC technologies are also discussed in detail. Graphical abstract: Dual-use open cycle ocean thermal energy conversion for adjustable production of electric power and desalinated water. Highlights: We examine performance of a dual-use open cycle OTEC. Steam flow fractions are important keys for maximum productions. Cold seawater intake rate primarily controls the pumping cost and production rates.